Effect of thyroid stimulating hormone on the prognosis of coronary heart disease - Ding, Ning; Hua, Rui; Guo, Hanqing; Xu, Yu; Yuan, Zuyi; Wu, Yue; Li, Ting (Frontiers in Endocrinology, 2025)
IntroductionClinical studies have shown that thyroid stimulating hormone (TSH) is associated with increased cardiovascular disease risk and mortality. Even within normal ranges, elevated TSH levels have an impact on the cardiovascular system and have been associated with cardiac dysfunction. The aim of our study was to evaluate the predictive value of admission fasting serum TSH levels in patients with coronary heart disease in relation to long-term major adverse cardiovascular events (MACE) and all-cause mortality.MethodA total of 3515 patients with coronary heart disease who met the inclusion criteria were divided into four groups according to the quantile of TSH levels: Group 1 (TSH, 0.34-1.02 mIU/L, n=878); Group 2 (TSH, 1.03-1.71 mIU/L, n=886); Group 3 (TSH, 1.72-2.84 mIU/L, n=880); and Group 4 (TSH, 2.86-5.50 mIU/L, n=873). MACE and all-cause mortality were also compared. TSH concentrations associated with the risk of MACE, all-cause mortality were assessed using continuous scales (restricted quartic splines) and Cox proportional hazards regression models.ResultsA total of 3515 patients with coronary heart disease were eligible for analysis. At a median follow-up of 70 months, patients in group 2 had a lower incidence of MACE compared to the other three groups. All-cause mortality was lower in the 3rd group. Restricted quartic spline analysis also revealed that TSH concentrations were associated with heart failure risk.DiscussionTSH levels have predictive value for adverse cardiovascular events and heart failure in patients with coronary heart disease.